Combination Antiretroviral Therapy for HIV in Rwandan Adults: Clinical Outcomes and Impact on Reproductive Health up to 24 Months - Brenda Asiimwe-Kateera; Nienke Veldhuijzen; Jean Paul Balinda; John Rusine; Sally Eagle; Joseph Vyankandondera; Julie Mugabekazi; Pascale Ondoa; Kimberly Boer; Anita Asiimwe; Joep Lange; Peter Reiss; et al. (AIDS Research and Treatment)
Adult women (n=113) and men (n=100) initiating combination antiretroviral therapy (cART) and women not yet eligible for cART (n=199) in Kigali, Rwanda, were followed for 6–24 months between 2007 and 2010. In the cART groups, 21% of patients required a drug change due to side effects and 11% of patients had virological failure (defined as >1,000 HIV RNA copies/mL) after 12 months of cART. About a third of the pregnancies since HIV diagnosis were unintended. The proportion of women in the pre-cART group using modern contraception other than condoms (50%) was similar to women in the general population, but this proportion was only 25% in women initiating cART. Of the women who carried at least one pregnancy to term since having been diagnosed HIV-positive, a third reported to have participated in a prevention-of-mother-to-child-transmission (PMTCT, option A) intervention. Many patients were coinfected with herpes simplex virus type 2 (79–92%), human papillomavirus (38–53%), and bacterial sexually transmitted infections (STIs) with no differences between groups. We applaud the Rwandan government for having strengthened family planning and PMTCT services and for having introduced HPV vaccination in recent years, but additional work is needed to strengthen STI and HPV-related cancer screening and management in the HIV-positive population.